The Syntactic Agreement of Verbs With Plural Controller Subjects in Najdi Arabic: An HPSG Approach - Alsanadi, Ruba A.; Althawab, Abdulrahman A. (Theory and practice in language studies, 2025)
Agreement is a rich area of debate that has continually proved to be a challenging topic for linguists. It interacts, among others, with syntax, semantics, morphology, pragmatics, and lexicology. Despite the complexity of the subject, it continues to be an essential part of research in linguistics, drawing attention to the intricate and nuanced aspects of languages. There is a wealth of literature on this topic. However, most previous studies have tended to focus on the core aspects of the phenomenon rather than the idiosyncratic ones, which, up to date, have not received proper attention from researchers in the field, especially in the field of modern linguistics. Hence, this paper aims to contribute to the growing understanding of the phenomenon by exploring an idiosyncratic topic in Najdi Arabic (NA) verb agreement, namely plural controllers. The topic will be described with a sufficient amount of data. In addition, the paper attempts to present a theoretical account of the relevant structures of plural controllers within the framework of Head-driven Phrase Structure Grammar (HPSG).